TEACHING WRITING BY USING PROCESS GENRE APPROACH TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 22 PALEMBANG - Hendri Saputra; Lenny Marzulina (Edukasi, 2015)
The objective of this study was to find out whether or not there is significant difference on students’ writing achievement taught by using Process Genre Approach and teacher’s strategy at the eighth grade students of SMPN 22 Palembang. The population of this study consisted of 277 eighth grade students of SMPN 22 Palembang in Academic Year of 2014/2015. There were 72 students taken as sample. Each class consisted of 36 students from class VIII.5 as control group and VIII.6 as experimental group. The sample of this study was taken by using convenience sampling method. In this study, the writer used quasi experimental design using nonequivalent pretest and posttest design. The instrument used in collecting the data was written test. The test was administered twice, as the pretest and posttest for both control and experimental group. The results of the test were analyzed by using IBM SPSS  (Statistical Package for the Social Science) Statistics 20. The result showed that teaching writing by using Process Genre Approach had significant difference on the students’ writing mastery. It can be seen from the result of pretest to posttest of each group. The achievement of experimental group was higher than the achievement of control group. Based on the result analysis of means significant difference from students’ posttest scores in control and experimental groups, it was found that t-obtained (0.000) was lower than t-table (0.05). So, the Ho (the null hypothesis) was rejected and Ha (the alternative hypothesis) was accepted. It means that there was significant difference on students’ writing achievement taught by using Process Genre Approach than students who are taught by using strategy that used by teacher.